2007
DOI: 10.1089/ten.2006.0423
|View full text |Cite
|
Sign up to set email alerts
|

The Sequential Expression Profiles of Growth Factors from Osteroprogenitors to OsteoblastsIn Vitro

Abstract: In this study, we delineate the sequential expression of selected growth factors associated with bone formation in vitro. Mineralization, osteocalcin, and alkaline phosphatase (ALP-2) were measured to monitor the differentiation and maturation of osteoprogenitor cells collected from C57BL mice. Bone-related growth factors, including transforming growth factor beta (TGF-beta), fibroblast growth factor 2 (FGF-2), platelet-derived growth factor (PDGF), insulinlike growth factor (IGF)-1, vascular endothelial growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
164
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 178 publications
(176 citation statements)
references
References 73 publications
9
164
1
2
Order By: Relevance
“…The release profile of OC demonstrated a detectable level at Day 15. OC levels remained high and increased continuously after Day 20, which agrees with previous experiments using similar conditions on culture plates alone [12].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The release profile of OC demonstrated a detectable level at Day 15. OC levels remained high and increased continuously after Day 20, which agrees with previous experiments using similar conditions on culture plates alone [12].…”
Section: Resultssupporting
confidence: 91%
“…Various growth factors, such as IGF-1 [30], IL-6 [32], BMP-2 [35,36], and CDMP-1 [31], were reported to enhance the effects of OP-1. Two recent studies reported FGF-2 also inhibited the stimulatory effects of OP-1 [4,14]; however, we found neither synergic nor antagonistic effects between OP-1 and FGF-2 in the present experiment, which is consistent with a previous in vivo study [12].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A recent study showed a decrease in IGF-1 mRNA levels parallel to the increase in the differentiation of the osteoblasts (26). Therefore, we can hypothesize that the gene expression of IGF-1 may be influenced by the composition of the culture medium and subsequently by the level of cell maturation.…”
Section: Discussionmentioning
confidence: 88%